Conducting fieldwork study in the Semai community: experiences and challenges / Hamimah Hamzah - Hamzah, Hamimah (2014)
This article will view experiences and challenges gained by the writer while conducting fieldwork study in completion her doctoral thesis at the International Islamic University Malaysia (IIUM). Conducting fieldwork study for the first time and having no skill in undertaking the study has turned the writer‟s life into nightmare. Indeed, this is true when the writer‟s application to conduct fieldwork research at Sg. Asap resettlement area in Belaga, Sarawak was turned down by the State Government of Sarawak without any valid reason. As a result, the writer almost gives up in continuing her study. Fortunately, after two years of study and with the supervisor encouragement and support she managed to change her research topic. This illustrated that conducting fieldwork study was challenges and burdensome task. To be succeeding in doing the fieldwork study, it is inadequate for a student to only be learned in the subject matter of the research. The student however, must have proper strategies and flexible plan and be prepared physically, mentally and financially while conducting the fieldwork study. As such, this article will address issues on preparing for the fieldwork, challenges on the field and the aftermath of the fieldwork.